Pemetaan Perkembangan Moral Mahasiswa Binus ditinjau dari Perspektif Kohlberg (Studi Kasus Terhadap 10 Mahasiswa di Kelas 04 Paf) - Esther Christiana; Nikodemus Thomas Martoredjo; Rina Patriana Chairiyani (Humaniora, 2013)
Learning means changing. Conditions of learning rely on a person's organizational thought against the learning process. One’s organizational thought is categorized into three major categories, each of which is divided into two phases: pre-conventional, conventional, and post-conventional. The teaching world, not least Bina Nusantara university, should play a role in developing the organizational thought /moral development of every person whom becomes the believer. This moral mapping may be information underlying the learning model. This mapping is generated through qualitative research of 10 Bina Nusantara university students, grade 04, PAF. Data collection technique used observational-partisipative method with the instrument of three moral dilemmas and Kohlberg’s moral stage development indicators. The results in the form of mapping of moral development is reported in the form of pie charts moral The study also resulted in the proposal of moral learning model that can be tested in subsequent research.